Factibilidad para la implementación de una planta procesadora de salchicha utilizando la miga del atún en la ciudad de Manta - Uquillas Zambrano, John Alejandro (2013)
The objective of this study was to determine the feasibility of implementing a sausage processing plant using tuna crumb Manta City. According to the investigation, the sausage had an acceptance of 86%, with demand of 20032.14 kg / month; it gaining market by testing important suggestions. The technical study determined the performance of the sausage with 96.5%, Chemical analyzes results obtained as 69.8% moisture, 3.09% ash, 2.07% fat, 12.8% protein and Microbiological: Salmonella, yeasts, fungi were negative, was established the optimal plant size at 250 m2 in total, as well as machinery and equipment require which it will have the capacity, availability and cost of raw materials ($ 2.50/kg). To determine the feasibility of the project calculated the net present value (NPV) is $ 312.477,25. The internal rate of return (IRR) with 34% had acceptable indicators, the balance point was 7214 units per month of packing of 200 g and the period of return on investment (PRI) that will be from the 5.16 years. Similarly, it is determined by the Leopold matrix of environmental impacts that obtained 34 impacts where there 18 were negative, at the stage of industrial process impacts 86 was obtained which there are 15 negative. Matrix evaluation showed that the project is feasible.